To believe or not believe in a just world? The psychological costs of threats to the belief in a just world and the role of attributions - Ramos, M. (2014)
Belief in a Just World (BJW) research has typically studied how individuals maintain and defend their beliefs from possible threats. However, none of this work has examined the psychological costs of threats to one's BJW. In the present research we tested its consequences on self-esteem. Focusing on threats related to relevant in-groups, we aimed to (1) understand the role of group identification in these processes and (2) identify the psychological mechanisms that can counteract their possible negative effects. In two studies we found that for individuals who were highly identified with the involved groups, perceiving a threat to their BJW led to low self-esteem. Conversely, we did not find such effects for low identifiers. Finally, we also found that causal attributions have a protective role in these processes. Results showed that in the face of a threat to BJW, making weaker internal attributions mitigates its harmful impact on self-esteem.